Reconstitution of Phase-Separated Signaling Clusters and Actin Polymerization on Supported Lipid Bilayers - Cheng, Xiaohang; Ullo, Maria F.; Case, Lindsay B. (Frontiers in Cell and Developmental Biology, 2022)
Liquid–liquid phase separation driven by weak interactions between multivalent molecules contributes to cellular organization by promoting the formation of biomolecular condensates. At membranes, phase separation can promote the assembly of transmembrane proteins with their cytoplasmic binding partners into micron-sized membrane-associated condensates. For example, phase separation promotes clustering of nephrin, a transmembrane adhesion molecule, resulting in increased Arp2/3 complex-dependent actin polymerization. In vitro reconstitution is a powerful approach to understand phase separation in biological systems. With a bottom-up approach we can determine the molecules necessary and sufficient for phase separation, map the phase diagram by quantifying de-mixing over a range of molecular concentrations, assess the material properties of the condensed phase using fluorescence recovery after photobleaching (FRAP), and even determine how phase separation impacts downstream biochemical activity. Here, we describe a detailed protocol to reconstitute nephrin clusters on supported lipid bilayers with purified recombinant protein. We also describe how to measure Arp2/3 complex-dependent actin polymerization on bilayers using fluorescence microscopy. These different protocols can be performed independently or combined as needed. These general techniques can be applied to reconstitute and study phase separated signaling clusters of many different receptors or to generally understand how actin polymerization is regulated at membranes.